A Bibliometric Analysis of Implementation PjBL-STEAM Model Over Past 11 Years - Irda Sukmawati Dewi; Wasis Wasis; Binar Kurnia Prahani; Imam Sya'roni; Neisya Azaria Adinda Putri; Noval Maleakhi Hulu (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study analyzes the development trends of STEAM-based project-based physics learning research over the past 10 years using bibliometric methods to describe (1) Research trends over the past 10 years; 2) Publication developments reviewed by document type, subject area, and language; 3) Distribution of research publications by country, author, and funding sponsor; and (4) identifying novelty between studies. Method: Research uses bibliometric analysis with descriptive qualitative interpretation of Scopus metadata. The analysis was conducted on 31 articles from Scopus and 17600 Google Scholar sources, with article categories, abstracts, and keywords covering the period 2015 to 2025. Results: The results of this study indicate that: a) The development of PjBL-STEAM physics learning research from 2015 to 2025, which was indexed in Scopus, was highest in 2024 with 10 publications. b) Various types of publication documents, namely conference reviews, conference papers, articles, and book chapters, with the dominant language used being English. c) Indonesia is the dominant country in conducting research publications, with Malang State University as the main contributor, along with the Malaysian University of Technology. d) Research on STEAM-based PjBL continues to experience innovations in accordance with the times. It leads to 21st-century skills and is applied in learning on topics such as physics applications, static fluids, and others. Novelty: Findings study in the first decade-scale (2015–2025) bibliometric analysis of PjBL-STEAM that integrates and compares data from Scopus and Google Scholar can improve quality education.